Improving the aerodynamic performance of a cycloidal rotor through active compliant morphing. (11th May 2017) - Ferrier, L.; Vezza, M.; Zare-Behtash, H.
ABSTRACT: Cycloidal rotors are a novel form of propulsion system that can be adapted to various forms of transport such as air and marine vehicles, with a geometrical design differing significantly from the conventional screw propeller. Research on cycloidal rotor design began in the early 1930s and has developed throughout the years to the point where such devices now operate as propulsion systems for various aerospace applications such as micro air vehicles, unmanned air vehicles and compound helicopters. The majority of research conducted on the cycloidal rotor's aerodynamic performance have not assessed mitigating the dynamic stall effect, which can have a negative impact on the rotor performance when the blades operate in the rotor retreating side. A solution has been proposed to mitigate the dynamic stall effect through employment of active, compliant leading-edge morphing. A review of the current state of the art in this area is presented. A two-dimensional, implicit unsteady numerical analysis was conducted using the commercial computational fluid dynamics software package STAR CCM+, on a two-bladed cycloidal rotor. An overset mesh technique, otherwise known as a chimera mesh, was used to apply complex transient motions to the simulations. Active, compliant leading-edge morphing is applied to an oscillating NACA 0015 aerofoil to attempt to mitigate the dynamic stall whilst maintaining the positive dynamic lift coefficient (Cl) contributions. It was verified that by applying a pulsed input leading-edge rotational morphing schedule, the leading-edge vortex does not fully form and the large flow separation is prevented. Further work in this investigation will focus on coupling the active, leading-edge motion to the cycloidal rotor model with the aim to maximise aerodynamic performance.